Magnesium-aluminum-erbium composite oxide catalyst as well as preparation method and application thereof
By using magnesium aluminum erbium composite oxide catalyst to prepare isophorone in the gas phase condensation reaction of acetone, the problems of low catalyst conversion rate, large number of by-products and easy catalyst deactivation in the existing technology are solved, and a high-efficiency, low-pollution process is achieved. Isophorone production.
Patent Information
- Application Number
- CN202411425365.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-12
AI Technical Summary
In the prior art, when acetone gas phase condensation method isophorone is prepared, the catalyst conversion rate is low, there are many by-products, and the catalyst is prone to deactivate, resulting in low production efficiency and heavy pollution.
Magnesium aluminum composite oxide catalysts are used to synthesize catalysts through water thermal method, and this catalyst is applied to the acetone gas -phase contraction reaction to optimize the reaction conditions to improve the conversion rate and selectivity.
Acetone conversion rate reaches more than 55%, the selectivity of heterolytone reaches more than 92%, which reduces the generation of by -products, and significantly improves the stability of the catalyst. It can maintain a high activity of 1,000 hours in continuous reactions.
Smart Images

Figure BDA0005081996530000101 
Figure BDA0005081996530000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of isophorone preparation, and specifically relates to a magnesium-aluminum-erbium composite oxide catalyst, a preparation method thereof and application thereof in catalyzing acetone condensation reaction to prepare isophorone. Background Art
[0002] Isophorone (3,5,5-trimethyl-2-cyclohexene-1-one) is an important fine chemical product. As a solvent, it has many advantages such as high boiling point, strong solubility, good dispersibility, and good leveling. Isophorone is widely used as an excellent solvent for some polymer materials, and has a wide range of applications in the polymer industry and the pharmaceutical industry. Isophorone is also an important organic synthesis raw material for the production of fine chemical products such as isophorone diamine and isophorone diisocyanate. In addition, isophorone can also be used to prepare 3,5-dimethylphenol insecticides, etc. Therefore, isophorone has broad application prospects.
[0003] Isophorone can be prepared mainly by two methods, one is the mesityl oxide method, and the other is the acetone condensation method. The mesityl oxide method uses mesityl oxide and ethyl acetoacetate as raw materials to obtain isophorone under the action of a catalyst. Due to the high production cost, this method is currently mainly in the laboratory stage and has not been industrialized (CN110885286A). The acetone condensation method is the main method for the current industrial synthesis of isophorone. In this method, three molecules of acetone generate one molecule of isophorone through a condensation reaction under the action of a catalyst.
[0004] Acetone condensation is divided into two methods: liquid phase condensation and gas phase condensation. In the liquid phase condensation method, inorganic strong bases such as sodium amide, calcium oxide (US2399976), alkali metals and alkaline earth metal hydroxides (US2344226, GB733650), or organic bases such as organic imidazole quaternary ammonium base (CN106892807A) are used as catalysts to prepare isophorone by heating the condensation reaction of acetone under high temperature conditions. In order to avoid stratification and promote full contact between acetone and the catalyst, a small amount of water is generally required to be added to the reaction system. With NaOH as the catalyst and 90% acetone aqueous solution as the raw material liquid, 14% acetone conversion and 51% isophorone selectivity can be obtained under 170°C (GB583863). With KOH as the catalyst, the reaction is carried out under about 200°C, and the acetone conversion and isophorone selectivity can reach 40% and 68% respectively (GB583863). The conversion rate of acetone and the selectivity of isophorone in the liquid phase condensation method are generally low. At the same time, this method also has the problems of difficulty in separating the catalyst from the product after the reaction, a large amount of alkali solution in the waste liquid, and heavy pollution. In the gas phase condensation method, solid alkali is generally used as a catalyst, and the reaction is carried out at 200°C to 400°C. This method can use a fixed bed reactor, which can be continuously produced and has many advantages such as simple separation process, high production efficiency, low pollution, and easy amplification. Using solid strong alkalis such as sodium methoxide as catalyst, in a fixed bed reactor, under the conditions of 110 to 280°C, the conversion rate of acetone is between 16 and 40%, and the optimal selectivity of isophorone does not exceed 70% (CN101050168A). Magnesium aluminum hydrotalcite can be used as a heterogeneous catalyst for preparing isophorone. In the test carried out in a tubular reactor, the conversion rate of acetone using magnesium aluminum hydrotalcite catalyst is 38%, and the selectivity of isophorone is 51% (US5849957). Aristech Chemical Corporation discloses the activity of some magnesium aluminum oxide catalysts in the preparation of isophorone (WO9012645, WO9507255). The conversion rate of acetone in the reaction is generally controlled below 35%. Too high acetone conversion rate will reduce the selectivity of isophorone and promote carbon deposition on the catalyst, thereby reducing the service life of the catalyst. When the conversion rate of acetone is 30%, the selectivity of isophorone can reach 76%. Using calcium aluminum oxide catalyst, the reaction at 300°C can achieve a total selectivity of mesityl oxide and isophorone of about 80% (US4535187).
[0005] In the acetone vapor phase condensation method, the byproducts are mainly mesityl oxide, mesitylene and tetramers and pentamers of acetone. In order to obtain higher selectivity of isophorone, it is generally necessary to control the conversion rate below 35%, which leads to the low production efficiency of isophorone. Even under the condition of lower conversion rate, the selectivity of isophorone is generally lower than 80%. On the other hand, the stability of most solid base catalysts is not good enough and is easily deactivated during the reaction. Therefore, it is still necessary to develop a catalyst with high activity and high stability to achieve efficient production of isophorone. Summary of the invention
[0006] The present invention aims at the deficiencies existing in the prior art and provides a process for preparing isophorone by gas phase condensation of acetone based on a magnesium-aluminum-erbium composite oxide catalyst. The method overcomes the disadvantages of the existing catalyst system, such as low conversion rate, many byproducts, and easy deactivation of the catalyst. The present invention has the advantages of simple catalyst preparation process, simple reaction process, continuous reaction, high conversion efficiency, high isophorone selectivity, high catalyst stability, etc.
[0007] One of the objects of the present invention is to provide a magnesium-aluminum-erbium composite oxide catalyst.
[0008] The second object of the present invention is to provide a method for preparing the magnesium-aluminum-erbium composite oxide catalyst.
[0009] The third object of the present invention is to provide an application of the magnesium-aluminum-erbium composite oxide catalyst.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] In a first aspect, the present invention provides a magnesium-aluminum-erbium composite oxide catalyst, wherein the composition of the magnesium-aluminum-erbium composite oxide catalyst is (MgO) x (Al2O3) y (Er2O3) z , where x:y=4:1~1:1, (x+2y):2z=100:1~10:1;
[0012] Preferably, x is 0.1-0.12, y is 0.04-0.05, and z is 0.002-0.0035.
[0013] In particular, the molar ratio of magnesium, aluminum, and erbium is 0.1:0.1:0.007;
[0014] Preferably, the specific surface area of the magnesium-aluminum-erbium composite oxide catalyst is 100 to 150 m 2 ·g -1 The average pore size is 5 to 20 nm, preferably 15 to 20 nm.
[0015] The catalyst comprises a composite oxide of magnesium oxide, aluminum oxide and erbium oxide.
[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned magnesium-aluminum-erbium composite oxide catalyst, comprising the following steps:
[0017] (1) dissolving soluble magnesium salt, aluminum salt and erbium salt in water to prepare a magnesium-aluminum-erbium mixed salt solution; in the magnesium-aluminum-erbium mixed salt solution, the molar ratio of magnesium to aluminum is 2:1 to 1:2, and the molar ratio of the sum of the amounts of magnesium and aluminum to the amount of erbium is 100:1 to 10:1; preferably, the molar ratio of magnesium, aluminum and erbium is 0.1:0.1:0.007;
[0018] (2) adding ammonia water dropwise to the magnesium-aluminum-erbium mixed salt solution under stirring, wherein the amount of ammonia water added is 1 to 3 times the theoretical amount of ammonia water required for complete precipitation of metal ions in the magnesium-aluminum-erbium mixed salt solution;
[0019] (3) After the addition of aqueous ammonia is completed, stirring is continued, and then the solution is transferred to a hydrothermal kettle for hydrothermal synthesis;
[0020] (4) After cooling, the precipitate is washed, separated, dried, and then calcined to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0021] The magnesium-aluminum-erbium composite oxide catalyst was synthesized by hydrothermal method.
[0022] Preferably, the magnesium salt in step (1) is one or more selected from magnesium nitrate, magnesium sulfate, magnesium chloride or magnesium acetate, preferably magnesium nitrate;
[0023] The aluminum salt is one or more selected from aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate, preferably aluminum nitrate;
[0024] The erbium salt is one or more selected from erbium nitrate or erbium acetate, preferably erbium nitrate;
[0025] Preferably, the molar concentration of the magnesium-aluminum-erbium mixed salt solution in step (1) is 0.5 to 2 mol / L.
[0026] Preferably, in step (2), the stirring temperature is 30-60° C., the dropping rate is 1-5 mL / min, and the mass concentration of the ammonia water is 10-40%, preferably 28%.
[0027] Preferably, in step (3), stirring is continued for 1 to 5 hours, the hydrothermal synthesis temperature is 120 to 200° C., and the hydrothermal synthesis time is 2 to 10 hours.
[0028] Preferably, in step (4), the drying temperature is 80-130° C., and the drying time is 4-20 h; the roasting temperature is 300-700° C., and the roasting time is 2-6 h.
[0029] More preferably, the magnesium-aluminum-erbium composite oxide catalyst is synthesized by a secondary hydrothermal method.
[0030] In some preferred embodiments, the method for preparing the magnesium-aluminum-erbium composite oxide catalyst comprises the following steps:
[0031] (1') dissolving soluble magnesium salt, aluminum salt and erbium salt in water to prepare a magnesium-aluminum-erbium mixed salt solution; in the magnesium-aluminum-erbium mixed salt solution, the molar ratio of magnesium to aluminum is 2:1 to 1:2, and the molar ratio of the sum of the amounts of magnesium and aluminum to the amount of erbium is 100:1 to 10:1; preferably, the molar ratio of magnesium, aluminum and erbium is 0.1:0.1:0.007;
[0032] (2') adding ammonia water dropwise to the magnesium-aluminum-erbium mixed salt solution under stirring, wherein the amount of ammonia water added is 1 to 3 times the theoretical amount of ammonia water required for complete precipitation of metal ions in the magnesium-aluminum-erbium mixed salt solution;
[0033] (3') After the addition of aqueous ammonia is completed, stirring is continued, and then the solution is transferred to a hydrothermal reactor for hydrothermal synthesis;
[0034] (4') washing and separating the precipitate after cooling;
[0035] (5') placing the precipitate in water, and adding ammonia water again, wherein the amount of ammonia water added is 30% to 60% of the amount of ammonia water used in the first titration. After the addition is completed, stirring is continued, and then the solution is transferred to a hydrothermal reactor for a second hydrothermal synthesis;
[0036] (6') stopping heating, cooling, washing, separating, drying, and then calcining the precipitate to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0037] Preferably, the magnesium salt in step (1') is one or more selected from magnesium nitrate, magnesium sulfate, magnesium chloride or magnesium acetate, preferably magnesium nitrate;
[0038] The aluminum salt is one or more selected from aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate, preferably aluminum nitrate;
[0039] The erbium salt is one or more selected from erbium nitrate or erbium acetate, preferably erbium nitrate;
[0040] Preferably, the molar concentration of the magnesium-aluminum-erbium mixed salt solution in step (1') is 0.5-2 mol / L.
[0041] Preferably, in step (2'), the stirring temperature is 30-60°C, the dropping rate is 1-5 mL / min, and the mass concentration of the ammonia water is 10-40%, preferably 28%.
[0042] Preferably, in step (3'), stirring is continued for 1 to 5 hours, the hydrothermal synthesis temperature is 120 to 160°C, and the hydrothermal synthesis time is 2 to 10 hours.
[0043] Preferably, in step (5'), the dropping rate is 1-5 mL / min, the mass concentration of ammonia water is 10-40%, preferably 28%, stirring is continued for 1-5 h, the secondary hydrothermal synthesis temperature is 160-200° C., and the secondary hydrothermal synthesis time is 2-10 h.
[0044] Preferably, in step (6'), the drying temperature is 80-130°C, and the drying time is 4-20 hours; the roasting temperature is 300-700°C, and the roasting time is 2-6 hours.
[0045] In a specific embodiment, the preparation method of the magnesium-aluminum-erbium composite oxide catalyst comprises the following steps:
[0046] 1. According to the formula, a certain amount of soluble magnesium salt, aluminum salt and erbium salt are weighed and dissolved in 150-250 mL of distilled water to prepare a 0.5-2 mol / L magnesium-aluminum-erbium mixed salt solution; wherein the molar ratio of magnesium to aluminum is 2:1-1:2, and the molar ratio of the sum of the amounts of magnesium and aluminum to the amount of erbium is 100:1-10:1;
[0047] 2. Keep the magnesium-aluminum-erbium mixed salt solution at 30-60°C, and add it dropwise to the magnesium-aluminum-erbium mixed salt solution at a drop rate of 1-5 mL / min under stirring. The amount of ammonia water added is 1-3 times the theoretical amount of ammonia water required for complete precipitation of metal ions in the magnesium-aluminum-erbium mixed salt solution;
[0048] 3. After the addition of ammonia water is completed, continue stirring for 1 to 5 hours, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 120 to 160°C for 2 to 10 hours for hydrothermal synthesis;
[0049] 4. After cooling to room temperature, wash, filter and centrifuge the precipitate, and stop washing when the filtrate reaches a pH value of 7;
[0050] 5. Put the precipitate into 150-250 mL of distilled water, and add 28% ammonia water at a drop rate of 1-5 mL / min again. The amount of ammonia water added is 30%-60% of the amount of ammonia water used in the first titration. After the addition is completed, continue stirring for 1-5 hours, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 160-200°C for 2-10 hours for secondary hydrothermal synthesis;
[0051] 6. Stop heating, cool to room temperature, wash, filter and centrifuge the precipitate, and stop washing when the filtrate reaches a pH of 7; dry the solid obtained after filtration in an oven at 80-130°C for 4-20 hours, and then calcine in a muffle furnace at 300-700°C for 2-6 hours under air atmosphere to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0052] The catalyst synthesized through the secondary hydrothermal process has a pore structure with a larger pore size, higher activity, and higher selectivity for isophorone.
[0053] In a third aspect, the present invention provides an application of the above-mentioned magnesium-aluminum-erbium composite oxide catalyst in the preparation of isophorone by gas phase condensation of acetone.
[0054] Preferably, the application comprises the following steps:
[0055] The magnesium-aluminum-erbium composite oxide catalyst is loaded into a fixed bed reactor, and acetone is used as a raw material at a reaction temperature of 200-400° C., a reaction pressure of 0.1-3 MPa, and a mass space velocity of 0.5-3 h -1 The reaction was carried out under the following conditions to obtain isophorone.
[0056] Preferably, the reaction temperature is 300°C, the reaction pressure is 0.1 MPa, and the mass space velocity is 1.2 h -1 .
[0057] Beneficial effects:
[0058] The magnesium aluminum erbium composite oxide catalyst prepared by the present invention is applied to the reaction of preparing isophorone by gas phase condensation of acetone, and can obtain about 92% isophorone selectivity under the condition of obtaining a high acetone conversion rate of more than 55%, greatly reducing the generation of by-products. At the same time, the catalyst has extremely high stability, and the catalytic activity does not significantly decrease in the continuous 1000h experiment. The present invention also has the advantages of simple catalyst preparation process, mild reaction conditions, and continuous reaction.
[0059] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0060] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0061] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0062] Preparation Example 1
[0063] Weigh 25.6 g of magnesium nitrate hexahydrate (0.1 mol), 37.5 g of aluminum nitrate nonahydrate (0.1 mol), and 3.2 g of erbium nitrate pentahydrate (0.007 mol), dissolve them in 207 mL of distilled water to prepare a 1 mol / L magnesium-aluminum-erbium mixed salt solution; keep the magnesium-aluminum-erbium mixed salt solution at 40° C., and under stirring, add 59 mL of 28% ammonia water dropwise to the magnesium-aluminum-erbium mixed salt solution at a drop rate of 2 mL / min; ; After the addition of ammonia water is completed, stirring is continued for 2 hours, and then the solution is transferred to a hydrothermal kettle, placed in an oven, and maintained at 140°C for 4 hours for hydrothermal synthesis; heating is stopped, and the precipitate is washed, filtered and centrifuged after cooling to room temperature. The washing is stopped when the filtrate is washed to a pH value of 7. The solid obtained after filtration is dried in an oven at 110°C for 12 hours, and then calcined at 500°C for 4 hours in an air atmosphere in a muffle furnace to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0064] Preparation Example 2
[0065] Weigh 25.6 g of magnesium nitrate hexahydrate (0.1 mol), 37.5 g of aluminum nitrate nonahydrate (0.1 mol), and 3.2 g of erbium nitrate pentahydrate (0.007 mol), dissolve them in 207 mL of distilled water to prepare a 1 mol / L magnesium-aluminum-erbium mixed salt solution; keep the magnesium-aluminum-erbium mixed salt solution at 40° C., and under stirring, add 59 mL of 28% ammonia water dropwise to the magnesium-aluminum-erbium mixed salt solution at a drop rate of 2 mL / min; ; After the addition of ammonia water is completed, stirring is continued for 2 hours, and then the solution is transferred to a hydrothermal kettle, placed in an oven, and maintained at 180°C for 4 hours for hydrothermal synthesis; heating is stopped, and the precipitate is washed, filtered and centrifuged after cooling to room temperature. The washing is stopped when the filtrate is washed to a pH value of 7. The solid obtained after filtration is dried in an oven at 110°C for 12 hours, and then calcined at 500°C for 4 hours in an air atmosphere in a muffle furnace to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0066] Preparation Example 3
[0067] Weigh 25.6 g of magnesium nitrate hexahydrate (0.1 mol), 37.5 g of aluminum nitrate nonahydrate (0.1 mol), and 3.2 g of erbium nitrate pentahydrate (0.007 mol), dissolve them in 207 mL of distilled water, and prepare a 1 mol / L magnesium aluminum erbium mixed salt solution; keep the magnesium aluminum erbium mixed salt solution at 40° C., and under stirring, add 59 mL of ammonia water with a mass concentration of 28% dropwise to the magnesium aluminum erbium mixed salt solution at a drop rate of 2 mL / min; after the addition of ammonia water is completed, continue stirring for 2 h, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 140° C. for 4 h for hydrothermal treatment. Synthesis; stop heating, cool to room temperature, wash, filter and centrifuge the precipitate, and stop washing when the filtrate reaches a pH of 7; put the precipitate into 200 mL of distilled water, and add 25 mL of 28% ammonia water at a drop rate of 2 mL / min again, and continue stirring for 2 hours after the addition is completed, then transfer the solution to a hydrothermal kettle, put it in an oven, keep it at 180°C for 4 hours, and perform secondary hydrothermal synthesis; dry the solid obtained after filtration in an oven at 110°C for 12 hours, and then calcine at 500°C for 4 hours in an air atmosphere in a muffle furnace to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0068] Preparation Example 4
[0069] Weigh 30.7 g of magnesium nitrate hexahydrate (0.12 mol), 30.0 g of aluminum nitrate nonahydrate (0.08 mol), and 3.2 g of erbium nitrate pentahydrate (0.007 mol), dissolve them in 207 mL of distilled water to prepare a 1 mol / L magnesium-aluminum-erbium mixed salt solution; keep the magnesium-aluminum-erbium mixed salt solution at 40° C., and under stirring, add 84 mL of 28% ammonia water dropwise to the magnesium-aluminum-erbium mixed salt solution at a drop rate of 2 mL / min; after the addition of ammonia water is completed, continue stirring for 2 h, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 140° C. for 4 h to perform hydrothermal heating. Thermal synthesis; stop heating, cool to room temperature, wash, filter and centrifuge the precipitate, and stop washing when the filtrate reaches a pH of 7; put the precipitate into 200 mL of distilled water, and add 30 mL of 28% ammonia water at a drop rate of 2 mL / min again, and continue stirring for 2 hours after the addition is completed, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 180°C for 4 hours to perform secondary hydrothermal synthesis; the solid obtained after filtration is dried in an oven at 110°C for 12 hours, and then calcined at 500°C for 4 hours in an air atmosphere in a muffle furnace to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0070] Preparation Example 5
[0071] Weigh 25.6 g of magnesium nitrate hexahydrate (0.1 mol), 37.5 g of aluminum nitrate nonahydrate (0.1 mol), and 1.9 g of erbium nitrate pentahydrate (0.004 mol), dissolve them in 204 mL of distilled water, and prepare a 1 mol / L magnesium aluminum erbium mixed salt solution; keep the magnesium aluminum erbium mixed salt solution at 40° C., and under stirring, add 58 mL of ammonia water with a mass concentration of 28% dropwise to the magnesium aluminum erbium mixed salt solution at a drop rate of 2 mL / min; after the addition of ammonia water is completed, continue stirring for 2 hours, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 140° C. for 4 hours for hydrothermal treatment. Synthesis; stop heating, cool to room temperature, wash, filter and centrifuge the precipitate, and stop washing when the filtrate reaches a pH of 7; put the precipitate into 200 mL of distilled water, and add 25 mL of 28% ammonia water at a drop rate of 2 mL / min again, and continue stirring for 2 hours after the addition is completed, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 180° C. for 4 hours to perform secondary hydrothermal synthesis; dry the solid obtained after filtration in an oven at 110° C. for 12 hours, and then calcine at 500° C. for 6 hours in an air atmosphere in a muffle furnace to obtain a magnesium-aluminum-erbium composite oxide catalyst.
[0072] Preparation Comparative Example 1
[0073] Weigh 25.6 g of magnesium nitrate hexahydrate and 37.5 g of aluminum nitrate nonahydrate, dissolve them in 200 mL of distilled water, and prepare a 1 mol / L magnesium-aluminum mixed salt solution; keep the magnesium-aluminum mixed salt solution at 40° C., and under stirring, dropwise add 56 mL of ammonia water with a mass concentration of 28% to the magnesium-aluminum mixed salt solution at a drop rate of 2 mL / min; after the dropwise addition of ammonia water is completed, continue stirring for 2 hours, then transfer the solution to a hydrothermal kettle, put it in an oven, and keep it at 140° C. for 4 hours; stop heating, cool to room temperature, wash, filter and centrifuge the precipitate, stop washing when the filtrate is washed to a pH value of 7, and dry the solid obtained after filtration in an oven at 110° C. for 12 hours, and then roast it at 500° C. for 4 hours in an air atmosphere in a muffle furnace to obtain a magnesium-aluminum composite oxide catalyst.
[0074] Preparation Comparative Example 2
[0075] Weigh 25.6 g of magnesium nitrate hexahydrate and 37.5 g of aluminum nitrate nonahydrate, dissolve them in 200 mL of distilled water to prepare a 1 mol / L magnesium-aluminum mixed salt solution; keep the magnesium-aluminum mixed salt solution at 40°C, and under stirring, add 56 mL of ammonia water with a mass concentration of 28% dropwise to the magnesium-aluminum mixed salt solution at a drop rate of 2 mL / min; after the addition of ammonia water is completed, continue stirring for 2 hours, then transfer the solution to a hydrothermal kettle, put it in an oven, keep it at 140°C for 4 hours, and perform hydrothermal synthesis; stop heating, cool to room temperature, and then perform The steps are washing, filtering and centrifugal separation, and the washing is stopped when the filtrate reaches a pH value of 7; the precipitate is placed in 200 mL of distilled water, and 25 mL of 28% ammonia water is added again at a dropping rate of 2 mL / min. After the addition is completed, stirring is continued for 2 hours, and then the solution is transferred to a hydrothermal kettle, placed in an oven, and maintained at 180°C for 4 hours for secondary hydrothermal synthesis; the solid obtained after filtration is dried in an oven at 110°C for 12 hours, and then calcined at 500°C for 4 hours in an air atmosphere in a muffle furnace to obtain a magnesium-aluminum composite oxide catalyst.
[0076] Application Example 1
[0077] The reaction was carried out in a fixed bed reactor, the fixed bed reaction tube was 40 cm long and 10 mm in inner diameter. The catalyst prepared in Preparation Example 1 was loaded into the fixed bed, and the catalyst loading amount was 1 g. The feed rate of acetone was 1.2 gh -1 , corresponding to a mass space velocity of 1.2 h -1 The reaction was carried out at a temperature of 300°C and a pressure of 0.1 MPa for 24 hours, and the reaction liquid at the 24th hour was sampled and analyzed. The reaction results are shown in Table 1.
[0078] Application Example 2
[0079] The experiment was carried out in the same manner as in Application Example 1, except that the loaded catalyst was changed to the catalyst prepared in Preparation Example 2. The reaction results are shown in Table 1.
[0080] Application Example 3
[0081] The experiment was carried out in the same manner as in Application Example 1, except that the loaded catalyst was changed to the catalyst prepared in Preparation Example 3. The reaction results are shown in Table 1.
[0082] Application Example 4
[0083] The experiment was carried out in the same manner as in Application Example 1, except that the loaded catalyst was changed to the catalyst prepared in Preparation Example 4. The reaction results are shown in Table 1.
[0084] Application Example 5
[0085] The experiment was carried out in the same manner as in Application Example 1, except that the loaded catalyst was changed to the catalyst prepared in Preparation Example 5. The reaction results are shown in Table 1.
[0086] Application Example 6
[0087] In addition to changing the acetone feed rate to 1.8gh -1 , mass airspeed changed to 1.8h -1 In addition, the experiment was carried out in the same manner as in Application Example 3. The reaction results are shown in Table 1.
[0088] Application Example 7
[0089] The experiment was carried out in the same manner as in Application Example 3 except that the reaction temperature was changed to 275°C. The reaction results are shown in Table 1.
[0090] Application Example 8
[0091] The experiment was carried out in the same manner as in Application Example 3 except that the reaction temperature was changed to 325°C. The reaction results are shown in Table 1.
[0092] Application Example 9
[0093] The experiment was carried out in the same manner as in Application Example 3 except that the reaction experiment was extended to 1000 h. The reaction liquid at 1000 h was sampled and analyzed, and the reaction results are shown in Table 1.
[0094] Application Comparative Example 1
[0095] The experiment was carried out in the same manner as in Application Example 1, except that the loaded catalyst was changed to the catalyst prepared in Preparation Comparative Example 1. The reaction results are shown in Table 1.
[0096] Application Comparative Example 2
[0097] The experiment was carried out in the same manner as in Application Example 1, except that the loaded catalyst was changed to the catalyst prepared in Preparation Comparative Example 2. The reaction results are shown in Table 1.
[0098] Table 1 Experimental results of application examples and comparative examples
[0099]
[0100]
[0101] Comparison of the experimental results of Example 1 and Comparative Example 1, and the experimental results of Example 3 and Comparative Example 2 shows that under the same catalyst preparation conditions, the magnesium-aluminum-erbium composite oxide catalyst has higher activity and selectivity for isophorone than the traditional magnesium-aluminum oxide catalyst. The specific surface areas of the catalysts corresponding to Preparation Examples 1-3 are 135, 128, and 115 m 2 g -1 , and the average pore diameters are 6.5, 7.0, and 16.6 nm, respectively. Compared with the catalyst synthesized by a single hydrothermal process, the specific surface area of the catalyst synthesized by the secondary hydrothermal process is slightly decreased, but the average pore diameter is greatly increased, indicating that the physical structure properties of the catalyst synthesized by the secondary hydrothermal process have undergone significant changes. From the experimental results of Application Examples 1-3, it can be seen that the catalyst synthesized by the secondary hydrothermal process has higher activity and selectivity for isophorone, indicating that the large-aperture pore structure can promote the diffusion process and the reaction.
[0102] The experimental results of Application Examples 3-5 show that the contents of the three components of magnesium, aluminum and erbium have a great influence on the catalytic activity. The appropriate relative content of magnesium, aluminum and erbium can greatly improve the conversion rate of acetone and the selectivity of isophorone. The experimental results of Application Examples 3 and Application Examples 6-8 show that the magnesium, aluminum and erbium composite oxide catalyst has a great influence on the catalytic activity at 300°C and a mass space velocity of 1.2h -1 The catalyst has good activity under the reaction conditions of , and can simultaneously obtain a high acetone conversion rate and isophorone selectivity. The experimental results of Application Example 3 and Application Example 9 show that the magnesium-aluminum-erbium composite oxide catalyst has high stability and no obvious deactivation occurs during the long-term reaction process.
[0103] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A magnesium-aluminum-erbium composite oxide catalyst, characterized in that: The composition of the magnesium-aluminum-erbium composite oxide catalyst is (MgO) x (Al2O3) y (Er2O3) z , where x:y=4:1~1:1, (x+2y):2z=100:1~10:
1.
2. The magnesium-aluminum-erbium composite oxide catalyst according to claim 1, characterized in that: The specific surface area of the magnesium-aluminum-erbium composite oxide catalyst is 100 to 150 m 2 ·g -1 The average pore size is 5 to 20 nm, preferably 15 to 20 nm.
3. A method for preparing the magnesium-aluminum-erbium composite oxide catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) dissolving soluble magnesium salt, aluminum salt and erbium salt in water to prepare a magnesium-aluminum-erbium mixed salt solution; in the magnesium-aluminum-erbium mixed salt solution, the molar ratio of magnesium to aluminum is 2:1 to 1:2, and the molar ratio of the sum of the amounts of magnesium and aluminum to the amount of erbium is 100:1 to 10:1; (2) adding ammonia water dropwise to the magnesium-aluminum-erbium mixed salt solution under stirring, wherein the amount of ammonia water added is 1 to 3 times the theoretical amount of ammonia water required for complete precipitation of metal ions in the magnesium-aluminum-erbium mixed salt solution; (3) After the addition of aqueous ammonia is completed, stirring is continued, and then the solution is transferred to a hydrothermal kettle for hydrothermal synthesis; (4) After cooling, the precipitate is washed, separated, dried, and then calcined to obtain a magnesium-aluminum-erbium composite oxide catalyst.
4. The preparation method according to claim 3, characterized in that: In step (1), the magnesium salt is one or more selected from magnesium nitrate, magnesium sulfate, magnesium chloride or magnesium acetate, preferably magnesium nitrate; The aluminum salt is one or more selected from aluminum nitrate, aluminum sulfate, aluminum chloride or aluminum acetate, preferably aluminum nitrate; The erbium salt is one or more selected from erbium nitrate or erbium acetate, preferably erbium nitrate; Preferably, the molar concentration of the magnesium-aluminum-erbium mixed salt solution in step (1) is 0.5 to 2 mol / L.
5. The preparation method according to claim 3, characterized in that: In step (2), the stirring temperature is 30-60° C., the dropping rate is 1-5 mL / min, and the mass concentration of the ammonia water is 10-40%.
6. The preparation method according to claim 3, characterized in that: In step (3), stirring is continued for 1 to 5 hours, the hydrothermal synthesis temperature is 120 to 200° C., and the hydrothermal synthesis time is 2 to 10 hours.
7. The preparation method according to claim 3, characterized in that: In step (4), the drying temperature is 80-130° C., and the drying time is 4-20 hours; the roasting temperature is 300-700° C., and the roasting time is 2-6 hours.
8. The preparation method according to claim 3, characterized in that: The preparation method of the magnesium-aluminum-erbium composite oxide catalyst comprises the following steps: (1') dissolving soluble magnesium salt, aluminum salt and erbium salt in water to prepare a magnesium-aluminum-erbium mixed salt solution; in the magnesium-aluminum-erbium mixed salt solution, the molar ratio of magnesium to aluminum is 2:1 to 1:2, and the molar ratio of the sum of the amounts of magnesium and aluminum to the amount of erbium is 100:1 to 10:1; (2') adding ammonia water dropwise to the magnesium-aluminum-erbium mixed salt solution under stirring, wherein the amount of ammonia water added is 1 to 3 times the theoretical amount of ammonia water required for complete precipitation of metal ions in the magnesium-aluminum-erbium mixed salt solution; (3') After the addition of aqueous ammonia is completed, stirring is continued, and then the solution is transferred to a hydrothermal reactor for hydrothermal synthesis; (4') washing and separating the precipitate after cooling; (5') placing the precipitate in water, and adding ammonia water again, wherein the amount of ammonia water added is 30% to 60% of the amount of ammonia water used in the first titration. After the addition is completed, stirring is continued, and then the solution is transferred to a hydrothermal reactor for a second hydrothermal synthesis; (6') stopping heating, washing, separating, and drying the precipitate after cooling, and then calcining it to obtain a magnesium-aluminum-erbium composite oxide catalyst; Preferably, the molar concentration of the magnesium-aluminum-erbium mixed salt solution in step (1') is 0.5 to 2 mol / L; Preferably, in step (2'), the stirring temperature is 30-60°C, the dropping rate is 1-5 mL / min, and the mass concentration of the ammonia water is 10-40%; Preferably, in step (3'), stirring is continued for 1 to 5 hours, the hydrothermal synthesis temperature is 120 to 160° C., and the hydrothermal synthesis time is 2 to 10 hours; Preferably, in step (5'), the droplet acceleration rate is 1-5 mL / min, the mass concentration of ammonia water is 10-40%, stirring is continued for 1-5 h, the secondary hydrothermal synthesis temperature is 160-200° C., and the secondary hydrothermal synthesis time is 2-10 h; Preferably, in step (6'), the drying temperature is 80-130°C, and the drying time is 4-20 hours; the roasting temperature is 300-700°C, and the roasting time is 2-6 hours.
9. Use of the magnesium-aluminum-erbium composite oxide catalyst according to claim 1 or 2 in the preparation of isophorone by gas phase condensation of acetone.
10. The use according to claim 9, characterized in that: The following steps are involved: The magnesium-aluminum-erbium composite oxide catalyst is loaded into a fixed bed reactor, and acetone is used as a raw material at a reaction temperature of 200-400° C., a reaction pressure of 0.1-3 MPa, and a mass space velocity of 0.5-3 h -1 The reaction was carried out under the following conditions to obtain isophorone.
Citation Information
Patent Citations
Method for preparing isophorone
CN101050168A
Isophorone preparation method
CN106892807A
Preparation method of alpha-isophorone
CN110885286A
Production of isophorone and homo-isophorones
GB583863A
Isophorone and its homologues
GB733650A